Gut Endocrine Regulation of Pediatric Growth and Weight: Integrating Intestinal Hormones, Inflammation, and the GH–IGF-1 Axis in Health and Disease - Ashraf T. Soliman; Fawzia Alyafei; Nada Alaaraj; Shayma Mohamed; Noor Hamed; Sohair Elsiddig (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: The intestine is increasingly recognized as an endocrine organ through enteroendocrine cells, gut-derived peptides, mucosal trophic factors, and microbiota–host signaling. In children, these pathways influence appetite, nutrient handling, body composition, and growth, including the growth hormone–insulin-like growth factor-1 (GH–IGF-1) axis. This review summarizes how intestinal endocrine function affects linear growth, weight gain, and GH–IGF-1 regulation in children with celiac disease, inflammatory bowel disease, environmental enteric dysfunction, and obesity. Discussion: Evidence supports a convergent model linking gut function to growth via gut hormone signaling (GLP-1, PYY, CCK, GLP-2, ghrelin), inflammation-driven GH resistance, and microbiota-mediated IGF-1 modulation. Celiac disease can cause growth failure reversible with a gluten-free diet; Crohn's disease impairs growth through inflammation and malabsorption; environmental enteric dysfunction drives population-level stunting; and in obesity, altered incretin responses highlight the intestine as a therapeutic target. Gut-endocrine pathways remain underutilized in pediatric practice. IGF-1 is frequently interpreted without accounting for mucosal inflammation or malabsorption, and cross-specialty fragmentation limits holistic growth assessment. Emerging therapies including GLP-2 analogues and incretin-based agents offer promise, though pediatric data remain limited. Standardizing gut-endocrine biomarkers and integrating intestinal health into growth frameworks are key research priorities. Conclusion: The intestine is a clinically important endocrine organ in pediatric growth medicine. Integrating gut-endocrine biology into endocrine assessment improves the interpretation of IGF-1 and growth patterns and guides management across undernutrition, chronic intestinal disease, and obesity.